PENGARUH ASAM GIBBERELAT DAN MEDIA TANAMTERHADAP PERTUMBUHAN PLANTULA PISANG PADATAHAP AKIMATISASI = EFFECT OF GIBBERELLIC ACID AND MEDIA ON BANANA PLANTLET GROWTH IN THE ACLIMATISATION - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The objective of' the research was to observe an optimum concentration of gibberellic acid (GA-3) solution and to find out an optimum media on banana s plantlet growth in the aclimatisation period. The research was carried out in the green house of Yogyakarta Agriculture Institute. The experimental design was RCBD factorial 3x2 With three replications. The first factor was three concentration factors divided into two kinds of media: soil + manure fertilizer 1:1 and soil + rices skin 1:1. The result of the experiment showed that the GA-3 solution concentration affected plants height. The optimum concentration was 50 ppm. In this corr